THE RESULTS OF STATE SUPPORT OF RESEARCH UNIVERSITY AND REAL SECTOR OF ECONOMY COOPERATION - Vladimir N. Korotaev (Высшее образование в России)
The article dwells upon the concept of science and innovation development at Perm National Research Polytechnic University, considers forms of interaction of science and innovation activities, reviews the main projects, realized at Perm Polytechnic University from 2010, considers creation of new elements of scientific and innovative infrastructure.